Keanekaragaman Dan Kelimpahan Gastropoda Di Pantai Bogak Indah Kecamatan Teluk Mengkudu Kabupaten Serdang Bedagai - Gusti Ayu Lestari; Agung Setia Batu Bara (CV.ITTC INDONESIA, 2024)
This research aims to determine whether there is a change in the composition of Gastropod species, whether there is a biodiversity index for Gastropod species and whether there is an abundance between natural micro-habitats, populated areas and ports. To obtain samples, the method used in this research was line and quadratic transects. The results of the research showed that the types of Gastropods obtained consisted of 4 orders. The total number of species is 17 with a total of 226 individuals. Gastropod diversity is classified as moderate. Shannon (H') = 2.225301. The highest abundance is at Bogak Indah Beach with a value of 117.3 ind/m2 and the lowest is in the port area of ​​Teluk Mengkudu District at 81.4 ind/m2. Gastropod uniformity is included in the uniform category with a uniformity index of 0.910. Gastropod dominance has a value of 0.144, which indicates that there are no species that dominate other species or that the community structure is in a stable state.